Adaptive strategy at the leaf level of Arbutus unedo L. to cope with Mediterranean climate - Gratani, Loretta; Ghia, Emanuela (Flora-Morphology, Distribution, Functional Ecology of …, 2002)
The adaptive strategy of Arbutus unedo L. under Mediterranean climate seemed to be due to the high leaf area (LA = 11.1 ± 0.1 cm2 ) increasing the potential capacity of light interception, the high leaf lamina thickness (L = 395 ± 10 µm) increasing the potential capacity for gas exchange, and the steeper leaf inclination at midday (α up to 63.9 ± 0.3°) determining 48% of reduction of incident radiation on a sloping leaf surface (RI), which could be a prevention mechanism against the potential photoinhibition of water-stressed leaves during drought. Nevertheless, during the drought period the photosynthetic activity and the water use efficiency (WUE) of A. unedo were strongly reduced (≥ than 50% of the maximum). Principal component analysis (PCA) underlined the higher similarity of A. unedo and Quercus ilex L. from a physiological point of view (photosynthetic rates PN , transpiration rates E, stomatal conductance gs , sub-stomatal CO2 concentration Ci ) and for leaf inclination, and with Cistus incanus L. from a phenological (leaf-life span) and structural point of view (specific leaf area SLA and leaf tissue density LTD), for leaf temperature (Tl ) and for leaf water status (leaf water potential at midday Ψmin and relative water content RWC). Therefore A. unedo might be considered in the borderline between drought semi-deciduous species and evergreen sclerophyllous species.
Keywords: Gas exchange; leaf area; leaf inclination; leaf lamina thickness; leaf-life span; sclerophylly

Adaptive strategy at the leaf level of Arbutus unedo L. to cope with Mediterranean climate (Flora-Morphology, Distribution, Functional Ecology of …, 2002)
The adaptive strategy of Arbutus unedo L. under Mediterranean climate seemed to be due to the high leaf area (LA = 11.1 ± 0.1 cm2 ) increasing the potential capacity of light interception, the high leaf lamina thickness (L = 395 ± 10 µm) increasing the potential capacity for gas exchange, and the steeper leaf inclination at midday (α up to 63.9 ± 0.3°) determining 48% of reduction of incident radiation on a sloping leaf surface (RI), which could be a prevention mechanism against the potential photoinhibition of water-stressed leaves during drought. Nevertheless, during the drought period the photosynthetic activity and the water use efficiency (WUE) of A. unedo were strongly reduced (≥ than 50% of the maximum). Principal component analysis (PCA) underlined the higher similarity of A. unedo and Quercus ilex L. from a physiological point of view (photosynthetic rates PN , transpiration rates E, stomatal conductance gs , sub-stomatal CO2 concentration Ci ) and for leaf inclination, and with Cistus incanus L. from a phenological (leaf-life span) and structural point of view (specific leaf area SLA and leaf tissue density LTD), for leaf temperature (Tl ) and for leaf water status (leaf water potential at midday Ψmin and relative water content RWC). Therefore A. unedo might be considered in the borderline between drought semi-deciduous species and evergreen sclerophyllous species.